Cardiac structure and function predicts functional decline in the oldest old. (29th August 2020) - Leibowitz, David; Jacobs, Jeremy M; Lande-Stessman, Irit; Gilon, Dan; Stessman, Jochanan
Abstract: Background: This study examined the association between cardiac structure and function and the deterioration in activities of daily living (ADLs) in an age-homogenous, community-dwelling population of patients born in 1920–1921 over a five-year follow-up period. Design: Longitudinal cohort study. Methods: Patients were recruited from the Jerusalem Longitudinal Cohort Study, which has followed an age-homogenous cohort of Jerusalem residents born in 1920–1921. Patients underwent home echocardiography and were followed up for five years. Dependence was defined as needing assistance with one or more basic ADL. Standard echocardiographic assessment of cardiac structure and function, including systolic and diastolic function, was performed. Reassessment of ADLs was performed at the five-year follow-up. Results: A total of 459 patients were included in the study. Of these, 362 (79%) showed a deterioration in at least one ADL at follow-up. Patients with functional deterioration had a significantly higher left ventricular mass index and left atrial volume with a lower ejection fraction. There was no significant difference between the diastolic parameters the groups in examined. When the data were examined categorically, a significantly larger percentage of patients with functional decline had an abnormal left ventricular ejection fraction and left ventricular hypertrophy. The association between left ventricular mass index and functional decline remained significant in all multivariate models. Conclusions: In this cohort of the oldest old, an elevated left ventricular mass index, higher left atrial volumes and systolic, but not diastolic dysfunction, were predictive of functional disability.